قرآن و سنت کی روشنی میں تجارت کے احکام و آداب:ایک مطالعہ: Rules and manners of trade in the light of Quran and Sunnah: A study - Dr. Syed Muhammad Nasim Sarwer (International Research Journal of Arabic and Islamic Studies, 2024)
A Muslim's life is adorned by the guidance of the Qur'an and the Sunnah. Explanation of Quranic rules is related to Sirat Tayyaba۔ The life of the Messenger of Allah Hazrat Muhammad (Peace be upon Him) is a pleasant and excellent example for the mankind. Therefore, the life of the Holy Prophet is ideal for every field. As a businessman, he proved to be the most honest and successful trader. Allah Almighty says in surah Al Baqarah, "O you, who believe, enter Islam wholeheartedly and do not follow the footsteps of Satan, for he is your open enemy." It is essential for every Muslim to abide by the Shari'ah rules and religious teachings in all his worldly and other affairs. It is not permissible for a Muslim to follow the Qur'an and Sunnah in worship, and to be self-sufficient in matters and social issues, and to consider himself free from Shari'ah restrictions. It is the specialty of our religion is that it contains a complete description of all kinds of matters of worship and business matters and issues. The Prophet Hazrat Muhammad (Peace be upon him) condemned all forms of trade which involve deception and fraud, lies and dishonesty, or distress and harm to the common people. Interpreted as deception and banned them. In this article, research and scientific study of the rules and etiquette of trade in the light of the Quran and the seerah of the Prophet (Peace be upon Him) has been done.